Clinical Evolution of Central Pontine Myelinolysis in a Patient with Alcohol Withdrawal: A Blurred Clinical Horizon - Abdul S. Mohammed; Prajwal Boddu; Dina F. Yazdani (Case Reports in Medicine)
Central pontine myelinolysis (CPM), a potentially fatal and debilitating neurological condition, was first described in 1959 in a study on alcoholic and malnourished patients. It is a condition most frequently related to rapid correction of hyponatremia. Chronic alcoholism associated CPM tends to be benign with a favorable prognosis compared to CPM secondary to rapid correction of hyponatremia. We describe a normonatremic, alcoholic patient who presented with CPM after a rapid rise in his sodium levels. Our case illustrates the fact that CPM can manifest even in patients who are normonatremic at baseline. Rapid rises in sodium levels should be promptly reversed before clinical symptoms manifest in patient with risk factors for CPM irrespective of their baseline sodium levels. Furthermore, clinical evolution of CPM can be difficult to discern from the natural course of alcohol withdrawal delirium, requiring astuteness and maintenance of a high degree of clinical suspicion on the part of the physician.